2020
DOI: 10.1002/bco2.50
|View full text |Cite
|
Sign up to set email alerts
|

The role of URO17™ biomarker to enhance diagnosis of urothelial cancer in new hematuria patients—First European Data

Abstract: Introduction and objectives Novel biomarker research is vital for the progression of safe and thorough diagnostic medicine. There is now a need to improve the diagnosis of bladder cancer via a noninvasive urine test while balancing the risks of harm from investigational procedures, such as cystoscopy and radiological tests, against the likelihood of malignancy. We evaluate the diagnostic accuracy and sensitivity of Uro17™ urinary biomarker for the detection of urothelial cancer in hematuria patients in a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Babu et al had identified high sensitivity and specificity of URO17 of 100% using urine samples in a retrospective study ( 44 ). Interestingly, URO17 is able to detect both low and high grade cancers in patients presenting with haematuria, a previously excluded cohort, thus proving its benefit of use in a surveillance setting as well ( 45 ). There is a specificity of 96 and 92.7% in recurrent and newly diagnosed patients, respectively ( 44 , 45 ).…”
Section: Promising Protein Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Babu et al had identified high sensitivity and specificity of URO17 of 100% using urine samples in a retrospective study ( 44 ). Interestingly, URO17 is able to detect both low and high grade cancers in patients presenting with haematuria, a previously excluded cohort, thus proving its benefit of use in a surveillance setting as well ( 45 ). There is a specificity of 96 and 92.7% in recurrent and newly diagnosed patients, respectively ( 44 , 45 ).…”
Section: Promising Protein Biomarkersmentioning
confidence: 99%
“…Interestingly, URO17 is able to detect both low and high grade cancers in patients presenting with haematuria, a previously excluded cohort, thus proving its benefit of use in a surveillance setting as well ( 45 ). There is a specificity of 96 and 92.7% in recurrent and newly diagnosed patients, respectively ( 44 , 45 ). Given these outcomes and its easy adaptation to current equipment used, a larger prospective study in a surveillance setting would be beneficial in developing this into a promising protein biomarker test for non-invasive surveillance of NMIBC ( 45 , 46 ).…”
Section: Promising Protein Biomarkersmentioning
confidence: 99%
“…Vasdev et al, 1 on a novel biomarker for urothelial cancer, and hence our theme of screening metrics. The cohort tested is a modest size of 71, but the overall sensitivity was 100% with specificity of 92.6%, and PPV 0f 95.7%.…”
Section: One Of Our Noteworthy Contributions Is From the United Kingdommentioning
confidence: 99%
“…8 ), shows promise in its diagnostic capability. This immunocytochemistry-based test detects the presence of oncoprotein Keratin 17 (K17)a protein involved in the replication cycle of malignant cells -in urothelial cells and has demonstrated a sensitivity of 100% in detection of both recurrent bladder cancer 9 and new bladder tumours from patients presenting with haematuria; the specificity of URO17 in the detection of recurrent and new bladder cancer was 96% and 92.6%, respectively 8 . These data suggest that URO17 could be a sensitive and specific test for papillary urothelial neoplasm of low malignant potential, as well as both papillary and nonpapillary carcinomas, providing diagnostic value in cases that could be missed by urine cytology.…”
Section: Wwwnaturecom/nrurolmentioning
confidence: 99%
“…Additionally, URO17 can be used to test patients presenting with haematuria, a cohort of patients that had not been included in previous studies of K17 tests, thereby expanding its use in the surveillance population. Notably, the immunocytochemical assay required for URO17 is easily adaptable to existing instruments and uses the same samples as used in urine cytology, thereby enabling its integration into clinical practice 8,9 .…”
Section: Wwwnaturecom/nrurolmentioning
confidence: 99%